1989
DOI: 10.1016/0014-5793(89)80225-x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a catalytically important residue of indoleglycerol‐phosphate synthase from Escherichia coli

Abstract: The active-site residues of indoleglycerol-phosphate synthase from Escherichia coli were tentatively localized by comparing crystallographic data with the amino acid identities among the known indoleglycerol-phosphate synthase sequences. To test the validity of the resulting model of catalysis one of the residues in the presumptive active site, Lys 55, was changed to serine using oligonucleotide-directed mutagenesis. The specificity constant k-,/K, of the mutant is 3 x l(Ptimes lower than that of the wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…5F). Previously, the role of Arg-182 was attributed to stabilization of the negatively charged carboxylate of CdRP (23). From MD structures, it is evident that the catalytically crucial Arg-182 plays an important role in the stabilization of the negatively charged phosphate moiety of IGPS.…”
Section: Lys-110-nhmentioning
confidence: 99%
“…5F). Previously, the role of Arg-182 was attributed to stabilization of the negatively charged carboxylate of CdRP (23). From MD structures, it is evident that the catalytically crucial Arg-182 plays an important role in the stabilization of the negatively charged phosphate moiety of IGPS.…”
Section: Lys-110-nhmentioning
confidence: 99%
“…An alternative hypothesis is that another active-site residue, such as Lys-53, also acts as a general acid, likely during the dehydration step. Indeed, site-directed mutagenesis of Escherichia coli IGPS demonstrated that Lys-53 (Lys-55 in E. coli IGPS) is highly important to IGPS catalysis (13). Lys-53 may also play roles in substrate binding and structural rearrangements occurring during catalysis.…”
mentioning
confidence: 99%
“…The conserved residues Lys53, Lys110, Glu159 and Asn180 (SsIGPS numbering) have been demonstrated essential for activity (corresponding to Lys63, Lys123, Glu172 and Asn194 in PaIGPS, Fig. 2) (11,12) and based on the SsIGPS-ligand structures, Lys110 was suggested to act as catalytic acid for both condensation and dehydration, while Glu159 was suggested to act as catalytic base in the dehydration step (7). Later, Zaccardi et al argued that it is unlikely for Lys110 to act as catalytic acid in both reaction steps since there is no clear mechanism for its reprotonation.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested catalytic residues (K123 and E172) according to Hennig et al(7) are marked with black asterisks and the alternative catalytic residues (K63 and E61) suggested by Zaccardi et al(13) by gray asterisks. Essential residues(11,12) are marked with red rings. The residue targeted for mutagenesis in this study is marked in a yellow box.…”
mentioning
confidence: 99%